Efficacy of Gooseberry, Tomato and Red Grapes Powder as Preservative in Restructured Chicken Block - Najeeb, A.P.; Mandal, P. K.; Pal, U. K. (Journal of Meat Science, 2015)
Use of natural preservatives to increase the shelf-life of meat products is promising because extracts or powders of many herbs, plants, vegetables and fruits have antioxidant and antimicrobial properties. Hence, the present study was planned to find out the effect of powders of red grapes, gooseberry and tomato on the quality and shelf life of restructured chicken block under refrigerated storage (7±1°C). Incorporation of powders at 1% level did not show any significantly effect on cooking yield (%) and proximate composition. A significantly (P
Keywords: Gooseberry; Tomato; Red grapes; Natural preservative; Restructured chicken block; Refrigerated storage; Biochemical quality